Dipolar Bose-Einstein condensates with large scattering length - Young-S, Luis E. [UNESP]; Adhikari, Sadhan Kumar [UNESP]; Muruganandam, P. [UNESP] (Amer Physical Soc, 2012)
A uniform dilute Bose gas of known density has a universal behavior as the atomic scattering length tends to infinity at unitarity while most of its properties are determined by a universal parameter xi relating the energies of the noninteracting and unitary gases. The usual mean-field equation is not valid in this limit, and beyond mean-field corrections become important. We use a dynamical model including such corrections to investigate a trapped disk-shaped dipolar Bose-Einstein condensate (BEC) and a dipolar BEC vortex for large scattering length. We study the sensitivity of our results on the parameter xi and discuss the possibility of extracting the value of this parameter from experimental observables.